Макросоциологический подход к выделению основных подсистем современной мировой системы обществ - Хуткий, Д.; Хмелько, В. (Социология: теория, методы, маркетинг, 2008)
Lack of a sufficiently complete knowledge about the composition of the modern world system of societies — especially about its subsystems — is one of the key problems of modeling of the modern world system of societies. Different criteria of discrimination of the main subsystems of the modern world system of societies from the macrosociological approach are analyzed in the issue. It is suggested to combine the two approaches to the division of the modern world system of societies into subsystems: (1) by the criterion of self-guidance and (2) by the criterion of specificity of functions of self-reproduction of the system. The systemic-functional substance of the processes of regulation and self-regulation of society as totality are considered. The phenomenon of self-guidance and the definition of the concept of society as self-guided social system are enucleated. It is demonstrated that as the result of decomposition of the modern world system of societies by the criterion of self-guidance certain as sociations of societies are discriminated as its first-order subsystems and individual societies are discriminated as its elements. And by decomposition of the modern world system of societies by the function criterion of the system self-reproduction we discriminate seven first-order functional subsystems, each consisting of specific second-order functional subsystems, each of which is divided into specific functional elements. It is also demonstrated, that the components of the modern world system of societies, discriminated by the criterion of self-guidance and by the function criterion of the system self-reproduction, are related in the following manner: any functional element of the modern world system of societies is a component of a certain society.